Blogging For Dummies / Susannah Gardner, Shane Birley, Safari - an O'Reilly Media Company. - Gardner, Susannah
This proven bestseller is fully updated and better than ever! Now in its fourth edition, Blogging For Dummies is fully updated and more practical than ever for today's bloggers. Whether you're just beginning or are already a full-tilt blogging maven, you'll find the up-to-date information you need in these friendly pages. Want to integrate your blog with social media? Jump into the fast-moving world of microblogging on Twitter or Tumblr? Choose which blogging software to use? Optimize your current blog for search? This detailed book guide covers it all, and then some. Buy the book, build a better blog, and blog about it! Provides up-to-date information on blogging software choices and utilities Explains how to identify your unique niche and attract readers Walks you through setting up an account and writing your first post Shows you how to optimize your blog for search, so new readers find you Helps you integrate your blog with social media Reveals what you need to know to start microblogging on Twitter or Tumblr Explores the ways you can make money with your blog Start a conversation with the very latest blog-building tips and techniques in Blogging For Dummies.